Redesain Pasar Klitikan Notoharjo Sebagai Pusat Perbelanjaan Barang Bekas Dikota SurakartaPendekatan Pada Desain Arsitektur Hijau) - SARLITO, SENO, Dr.Ir. Qomarun, MM, M.S Priyono Nugroho, ST, MT (2015)
Traditional markets are trading sector has its own characteristics which the patterns of interaction between sellers and buyers, as well as play an important role in the developments in Indonesia's economy. Village of clover is one of 51 villages in Kota Surakarta.merupakan trade area one of which is the market Klitikan Notoharjo. container for street merchants selling various used goods. The market building is a building Klitikan Notoharjo categorized including new buildings paddock pemeriantah Surakarta city's new building since tahasiaonal un 2006. Since this building stood until now there has been no improvement since the building is still relatively new, but after a full evaluation author habitation in buildings Notoharjo Klitikan market, ternayata there are many or most of the things that should be on redesigning back. Penilis concept architectural emphasis emphasize on building market is Klitikan Notoharjo. The concept of 'green architecture' or green architecture becomes a topic of current interest, one of them because of the need to empower the potential of the site and save natural resources as a result of the depletion of non-renewable energy sources. Various thoughts and interpretations architect bermunculuan differently, each caused by contact with the professional conditions they face. The concept of 'green' can also be applied to the reduction of energy use (eg electrical energy), low energy and zero energy house building to maximize the cover of the building (building envelope). Use of renewable energy such as solar energy, water, biomass, and waste-to-energy also noteworthy.